2022
DOI: 10.1111/joss.12768
|View full text |Cite
|
Sign up to set email alerts
|

How to inform about sodium reduction on food labels?

Abstract: Excessive sodium intake is a worldwide problem. Little attention has been paid to consumer perceptions and thoughts on how to report sodium reduction in food packaging. We aimed to investigate the opinion of consumers on the best ways to inform about sodium reduction on food labels. We held focus group sessions and performed a modified choice based conjoint analysis. Participants prefer packaging that has the front of pack nutrition label traffic light labeling and use of sentences informing the percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Package characteristics were defined based on previously studies (Sant'anna et al, 2022), in which consumers' behavior and opinion about the package of low‐sodium products through focus group sessions were evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Package characteristics were defined based on previously studies (Sant'anna et al, 2022), in which consumers' behavior and opinion about the package of low‐sodium products through focus group sessions were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Sant'anna et al (2022) found that consumers would prefer a package of low‐sodium products to have different colors from the package of traditional products, and blue was the most mentioned for this type of product. As for the way to get information about sodium reduction, consumers prefer information that shows the reduction percentage to assess whether the reduction is significant or not.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A basic idea in this research is that consumers respond with a positive feeling of calmness to cool colors, whereas warm colors are more likely to be associated with arousal and attention. Correspondingly, cool packaging colors have been associated with higher health perceptions than warm packaging colors in most but not all studies examining health perceptions [6,[14][15][16][17]. Below, we describe the studies comparing the effects of warm vs. cool colors on health perceptions in detail.…”
Section: Warm Vs Cool Color Huesmentioning
confidence: 99%